Of Slide Rules and Stethoscopes: AI and the Future of Doctoring - Truog, Robert D. (The Hastings Center report, 2019)
Historically, the practice of medicine has been a physically intimate endeavor. Physicians have used their hands to palpate and reveal the secrets hidden within the body. Smelling the breath for the ketosis of diabetes or tasting the skin for the saltiness of cystic fibrosis were among the physician's essential practices. Today, perhaps the most defining characteristic of a brilliant clinician is the ability to synthesize many images—from electrocardiograms, ultrasounds, CT scans, and so forth—into a coherent picture that can guide our diagnosis and treatment. Yet this is rapidly becoming a Sisyphean task. Just as we are about to drown in a deluge of data, AI is throwing us a life preserver, to save not only our patients but ourselves. But where will AI take us?